Application Of Perineum Wound Healing With Binahong Leaf Boiled Water And Fishcork Extract - Eni Indrayani; Hastin Ika Indriyastuti; Medzelia Efenti Lestari (Prosiding University Research Colloquium, 2022)
Background: Postpartum mothers usually have perineal wound. Perineal wound is perineal tearduring delivery process. It occurs in almost all first deliveries and also many happen to subsequentdeliveries. To hande (or to heal) perineal wound, it can be done by applying binahong leaf boiledwater and fishcork extract.Objective: To determine the acceleration of the perineal wound healing of postpartum mothers byusing binahong leaf boiled water and fishcork extract..Method: This research is a qualitative descriptive with a case-study approach.The participants were24 postpartum mothers who met the inclusion criteria. The instruments used were observationsheets, reeda scala sheets and a camera. The data were obtained through interview, observation, anddocumentation.Results: after being given boiled water from binahong leaves and snakehead fish extract for 7 days to24 participants, 20 people (83.3%) healed on day 6 and 4 people (16.7%) healed on day 7. Woundhealing time an average of 6.15 days has experienced faster unification. The effectiveness of boiledwater from binahong leaves on the healing of perineal rupture in 24 respondents showed that 83.3%of perineal rupture healed in the fast category (< 6 days).Conclusion: The application of boiled water of binahong leaf and extract of fishcork can helppostpartum mothers heal their perineal wounds.